Spatial variation in life-history traits of Oithona spp. in a shallow temperate estuarine system (Río de la Plata, south-west Atlantic) during spring - Cepeda, Georgina Daniela (2015)
Oithonid species are key components of estuarine zooplankton communities. The spatial distribution of Oithona nana and O. helgolandica (syn. O. similis) and their population dynamics were studied for the first time in a shallow temperate estuarine system in the south-west Atlantic Ocean. Here we estimated the influence of physical (salinity and temperature) and trophic (chlorophyll-A and bacterioplankton concentrations) factors on the life-history traits of O. nana and O. helgolandica. The abundance and biomass of O. nana were higher at the surface salinity front but were not correlated with higher egg production rates, which suggests the presence of some retention mechanism that favours population aggregation. In a spatial context, the high reproductive activity near the La Plata River runoff in comparison with the coastal system nearby, suggests that this system might favour the proliferation of O. nana populations. However, smaller females with fairly few and smaller eggs per sac occurred under estuarine influence, which implies that there is a potential ecological advantage. The extremely low abundance and reproductive activity of O. helgolandica at the Río de la Plata system indicates that this system might not constitute the best habitat for this cyclopoid.